Microstructural Characterisation, Modelling and Simulation of Solid Oxide Fuel Cell Cathodes - Joos, Jochen (Schriften des Instituts für Angewandte Materialien - Werkstoffe der Elektrotechnik, Karlsruher Institut für Technologie / Institut für Angewandte Materialien - Werkstoffe der Elektrotechnik, 2017)
This work deals with microstructural characterisation, modelling and simulation of SOFC electrodes with the goal of optimizing the electrode microstructures. Methods for a detailed electrode analysis based on focused ion beam (FIB) tomography are presented. A 3D FEM model able to perform simulations of LSCF cathodes based on 3D tomography data is shown. A model generating realistic, yet synthetic microstructures is presented that enables the optimization of microstructural characteristics.